The Need for Retirement Planning and Counselling - Perry, Glenys (Canadian Journal of Counselling and Psychotherapy, 2012)
This article discusses some of the problems related to retirement. It also describes three factors that influence successful adjustment to retirement. These three major factors include (a) having retirement plans, (b) having positive attitudes toward retirement, and (c) having a realistic picture of what retired life is like. Since counselling may aid in achieving each of these elements the role of the counsellor is also discussed with special emphasis being placed on the need for counsellors to have an accurate perception of what retired life is actually like.